Advance in the Role of Epigenetic Reprogramming in Somatic Cell Nuclear Transfer-Mediated Embryonic Development - Xiaolei Zhang; Shaorong Gao; Xiaoyu Liu (Hindawi Limited, 2021)
Somatic cell nuclear transfer (SCNT) enables terminally differentiated somatic cells to gain totipotency. Many species are successfully cloned up to date, including nonhuman primate. With this technology, not only the protection of endangered animals but also human therapeutics is going to be a reality. However, the low efficiency of the SCNT-mediated reprogramming and the defects of extraembryonic tissues as well as abnormalities of cloned individuals limit the application of reproductive cloning on animals. Also, due to the scarcity of human oocytes, low efficiency of blastocyst development and embryonic stem cell line derivation from nuclear transfer embryo (ntESCs), it is far away from the application of this technology on human therapeutics to date. In recent years, multiple epigenetic barriers are reported, which gives us clues to improve reprogramming efficiency. Here, we reviewed the reprogramming process and reprogramming defects of several important epigenetic marks and highlighted epigenetic barriers that may lead to the aberrant reprogramming. Finally, we give our insights into improving the efficiency and quality of SCNT-mediated reprogramming.